Spatially Resolving Polymer Brush Conformation: Opportunities Ahead - Besford, Quinn A.; Uhlmann, Petra; Fery, Andreas (Macromolecular Chemistry and Physics, 2023)
Surfaces that respond to local environmental stimuli offer intriguing possibilities for new surface-based sensing concepts to emerge. An attractive concept is to push beyond the milli- to micrometer lateral resolution limit in sensing, toward the ultimate surface-sensitive device; one capable of real-time sensing of the nanoscopic, or molecular “touch.” This sensing needs an approach that is capable of spatially transducing information on nanotouch. Polymer brushes are a class of surface that provides dramatic changes in surface properties depending on stimuli that affect the conformation of end-tethered polymer chains. However, the brush response is typically quantified by measuring changes in polymer brush “height”. That is, the ensemble average distance over which polymer density exists away from the anchoring surface (i.e., a single parameter to describe the surface). Moving beyond this conceptual paradigm of quantifying the ensemble average height in a single dimension over the entire surface under applied stimuli, developing methods for spatially resolving chain conformation has the very real potential to lead to extraordinary possibilities in the applied sciences. In this perspective, the current paradigms and methods forward for extracting rich details on polymer brush conformational dynamics that is spatially resolved, which can lead to new understandings of surface contact, are discussed and pointed out.
CRIS-Team Scopus Importer:2023-03-20
Keywords: conformational transitions; polymer brushes; sensing; spatially resolved